Optimasi Bahan Organik untuk Meningkatkan Hasil Bawang Merah yang Dipupuk Biosulfo - Sudadi Sudadi; Demelia Arida Ariyanti (Faculty of Agriculture, Universitas Sebelas Maret, 2012)
Tittle : Optimization of Biosulfo Formula Fertilizer Dose and Organic Matter for P uptake, and S and Yield of Red Onion (Alium ascolonicum L.) at Acid Soil, Neutral and Alkalis. The purpose of this study is to determine the effect and optimum dosage biosulfo fertilizer and organic matter on the results of red onion on the acid soils, neutral and alkaline. This research was conducted at Field Experiment station of the Agriculture Faculty of Sebelas Maret University Surakarta at Jumantono, Karanganyar, on September until December 2009. This research Experiments arranged in factorial Completely Randomized Design Association (CRD) with three factors, icluded type of soil, Alfisol (T1), Entisol (T2), and Vertisol (T3), the dose biosulfo fertilizer of 0% dose of SP-36 (P0), 100% dose of SP-36 (P1) and 200% dose of SP-36 (P2 ), and dose of organic matter of 0 tons/ha (B0),5 tons/ha (B1) and 10 tons/ha (B2). Each treatment combination was replicated three times. This research was used polybags a size 40 x 50 cm. Each polybags were taken 10 me and planted with two seeds or red onion. The observed variables were available P and S, P and S uptake and onion yield. Data analysis used F test at 95% and to compare inter treatment average used DMRT test (normal data), Kruskal Wallis test (unnormal data) at 95% and Mood Median test, to determine fertilizer optimum dose used Surface Response test (Regression) and Correlation test to know closely correlation on inter variable. The result showed that the highest P uptake at Alfisol (0,009 gr P/plant) was taken at the application of biosulfo equivalent with 900 kg/ha SP36, at Entisol (0,074 gr P/plant) at the application of 10 ton/ha organic matter, and Vertisol (0,027 gr P/plant) was taken for the application of biosulfo equivalent with 760 kg/ha SP36, respectively. The highest S uptake at Alfisol (0,20 gr S/plant) was taken the application of 10 ton/ha organic matter, at Entisol (2,104 gr S/plant) at the application of biosulfo equivalent with 850 kg/ha SP36, and Vertisol (1,671 gr S/plant) at the application of 10 ton/ha organic matter, respectively. The highest of union yield at Alfisol (10,82 gr/plant) was taken at the application of biosulfo equivalent with 900 kg/ha SP36, at Entisol (83,7 gr/plant) at the application of 10 ton/ha organic matter, and Vertisol (78,8 gr/plant) was taken for the application of 10 ton/ha organic matter, respectively.